The influence of gender upon women business-owners’ access to debt finance in Bangladesh, a patriarchal developing nation - Jaim, Jasmine (2016)
There is growing attention to analyse the influence of gender upon women’s entrepreneurship. Nonetheless, the body of literature almost entirely concentrates on developed nations, specifically on the USA and Europe. The research context for the thesis is Bangladesh, a South Asian developing nation, where there was a government initiative to support small businesses of women through bank loans.